Pengaruh Iklan Politik Partai Dan Citra Kandidat Terhadap Sikap Memilih : (Studi Terhadap DPW Partai Nasdem Provinsi Gorontalo) - Abdul Rajak Babuntai (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
In every general election, various party political advertisements appear to persuade voters to give their support. In addition, the candidate's image is made as good as possible to meet the tastes of voters so that voters provide support to the candidate. This research was conducted to determine the effect of party political advertising and candidate image on voting attitudes of people in the city of Gorontalo. This study used a quantitative approach with explanatory survey methods. Data was collected using a questionnaire. The sample in this study were 383 residents of the city of Gorontalo and were taken using the Proportional Stratified Random Sampling technique. Data analysis in this study used Partial Least Square (PLS) with the help of the SmartPLS version 4 software program. The findings of this study indicate that there is no effect of party political advertising on voting attitudes of the people of Gorontalo city, candidate image has a significant effect on the voting attitude of the people of Gorontalo city and there is a difference in the effect of party political advertising and candidate image on voting attitudes of the people of Gorontalo city.